Inside The Gay Homosociality: Skrip Seksual Dan Dominasi Maskulinitas Dalam Ruang Lingkup Pertemanan Antarsesama Gay - Fitri Ayunisa (Antropologi Indonesia, 2021)
Three categories of identity among gays, namely top, bottom, and versatile embodied in the different roles in sexual activity, were also motivated by differences in characteristics and specific friendship patterns in daily life. Until now, discrimination in heterosexual social relations is still experiencing by most homosexuals has triggered the formation of gay homosociality. Besides, proving self-existence, the friendship between gays is also a way to get social support and entertainment from the pressure of heterosexual friendship routines. The subjects involved in the study included eight people with different gay sexual identities, consisting of 4 bottoms, 2 tops, and 2 versatiles. The diversity of the subject identity attempts to understand the influence of sexual scripts in regulating gay homosociality patterns and is used as guidelines for behaving gays in everyday life. The dominance of masculinities in gay homosociality influences the gender gay norms in daily performativity. Gay homosociality also serves as a gender norm and social control among members.